Financiamento e gasto público da assistência social no Município de Vitória-ES, 2005 a 2012 - Taufner, Ingrid Mischiatte (2013)
This paper addresses the public funding and expenses with the social service policy in the municipality of Vitória (state of Espírito Santo, Brazil) in the eight following years after the publication of the National Policy of Social Assistance 2004. This research is a case study, based on a review of the literature and documental investigation, utilizing as source of the data acquired the municipal system of Budgetary Control Tool, the Municipal Plans of Social Assistance, the Multi-year Plans of Application and other laws and municipal resolutions. It also presents considerations regarding the journey of the social assistance, especially after the Federal Constitution of 1988. It discusses aspects of the fiscal policy, of the public budget, of the Fiscal Responsibility Law and of the funding and expenses of the Federal Government to the social assistance. Finally, it analyzes the experience of the municipality of Vitória - ESo. In this paper, social assistance is understood as one of the ways of state intervention, in the sense of guaranteeing the reproduction conditions of the capitalist society, whether contributing to the accumulation of capital or responding to the claims of workers. Results show that it was possible to identify advances and limitations on funding and expenses with the social assistance policy in the referred municipality. Among these, it can be highlighted, on one hand that social assistance funds were extended in real values and the municipality leading role in policy funding also became more evident. On the other hand, it also stands out the maintenance and/or percentage expenses reduction in relation to the general expenses of the municipality, and the insufficient contribution of resources to make social assistance get ahead, aiming service extension and qualification.